2013
DOI: 10.3746/jkfn.2013.42.1.026
|View full text |Cite
|
Sign up to set email alerts
|

Fingerroot (Boesenbergia pandurata) Extract Inhibits the Accumulation of Visceral Fat in C57BL/6J Mice

Abstract: Boesenbergia pandurata (Roxb.) Schltr. has been reported to possess anti-oxidative and anti-inflammatory properties. The aim of this study was to investigate the effect of Boesenbergia pandurata extract (BPE) in a high-fat diet (HFD)-induced obese mice model. C57BL/6J mice were fed with either the high-fat diet or a 0.5% BPE-supplemented HFD for 8 weeks. The BPE-containing HFD significantly reduced body weight gain and the accumulation of visceral fat mass in mice model without altering the amount of food inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Interestingly, several dietary supplements for weight loss in the market indicate fingerroot as the main active ingredient [29]. Studies on high-fat-diet mice indicated that fingerroot extracts prepared from the materials collected from Indonesia could reduce body weight gain by decreasing the accumulation of visceral fat [26,30,31]. Pandurantin A was found to be the major component (0.8% w/w based on dried weight) and was shown to suppress adipogenesis in mouse pre-adipocytes via regulating AMP-activated protein kinase (AMPK) and PPARα/δ signals [26].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several dietary supplements for weight loss in the market indicate fingerroot as the main active ingredient [29]. Studies on high-fat-diet mice indicated that fingerroot extracts prepared from the materials collected from Indonesia could reduce body weight gain by decreasing the accumulation of visceral fat [26,30,31]. Pandurantin A was found to be the major component (0.8% w/w based on dried weight) and was shown to suppress adipogenesis in mouse pre-adipocytes via regulating AMP-activated protein kinase (AMPK) and PPARα/δ signals [26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have indicated fingerroot extract’s anti-adipogenic and anti-obesity properties over the past decade. Mechanisms such as activated protein kinase, regulation of lipid metabolism, reduced triglyceride, and increased HDLC4 were identified in rodent models with high-fat diets [46] , [47] , [48] . This toxicity study provides valuable insights and directs the future research of the fingerroot extract formulation.…”
Section: Discussionmentioning
confidence: 99%